External ureteric stent versus internal double J stent in kidney transplantation: a retrospective analysis on the incidence of urological complications and urinary tract infections - Hazenberg, Ietje T.; Middelkoop, Stephanie J. M.; de Joode, Anoek A. E.; Rabbeljee, Juliette D.; Pol, Robert A.; Doornweerd, Benjamin H. J.; Sanders, Jan-Stephan F.; Stegeman, Coen A. (Frontiers in Nephrology, 2023)
Introduction Urologic complications (UCs) and urinary tract infections (UTIs) are common after kidney transplantation. Intraoperative stent placement at the vesicoureteric anastomosis reduces UC risk, but increases UTI risk. Methods In 2014 our stenting protocol changed from external ureteric stent (ES) to internal double J stent (DJ). We retrospectively studied the occurrence of UCs and UTIs in relation to ES or DJ in 697 kidney recipients. Methods An ES was used in 403 patients (57.8%), in 294 (42.2%) a DJ. ES was removed 7-12 days and DJ 3-4 weeks post-operative. Induction immunosuppression was the same in both groups. Primary outcomes at 6 months follow-up were UC (urinary leakage/ureter stenosis) and UTI; they were related to stenting procedure and clinical and transplant characteristics. The incidence of UCs was similar for ES (8.4%) and DJ (6.8%), p=0.389. ES use was a significant risk factor for UTI (OR 1.69 (1.15-2.50), p=0.008). Post-transplant hospitalization was significantly shorter in the DJ group. Despite more acute rejection episodes with ES (ES/DJ: 16.4%/6.1%, p<0.001), no clinical relevant differences in graft outcomes existed. Discussion A DJ is, compared to ES, associated with a lower incidence of UTIs and comparable occurrence of UCs and is therefore the preferred technique for stenting the vesicoureteric anastomosis.